2019
DOI: 10.1101/748368
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bivariate analysis of barley scald resistance with relative maturity reveals a new major QTL on chromosome 3H

Abstract: 1 6

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…The sequences of markers associated with the identified QTLs for scald resistance were used to perform BLAST searches by using the IPK Barley BLAST Server (http://webbl ast.ipk-gater sleben.de/barley). The barley pseudomolecules Morex v. 2.0 2019 were used for the BLASTn search (Zhang et al, 2019;Leng et al, 2020). Default settings were used to do the BLASTn search and the best hit was used to decide the physical position of the detected QTL (Table 1 and Figure 2).…”
Section: Ma Jor G Ene S and Lo CI Identified For Sc Ald Re S Is Tan Ce In Barle Ymentioning
confidence: 99%
See 1 more Smart Citation
“…The sequences of markers associated with the identified QTLs for scald resistance were used to perform BLAST searches by using the IPK Barley BLAST Server (http://webbl ast.ipk-gater sleben.de/barley). The barley pseudomolecules Morex v. 2.0 2019 were used for the BLASTn search (Zhang et al, 2019;Leng et al, 2020). Default settings were used to do the BLASTn search and the best hit was used to decide the physical position of the detected QTL (Table 1 and Figure 2).…”
Section: Ma Jor G Ene S and Lo CI Identified For Sc Ald Re S Is Tan Ce In Barle Ymentioning
confidence: 99%
“…Looseley et al (2012) detected QTLs based on the amount of R. commune in symptomless leaves, with results showing that the amount of R. commune in symptomless leaves is correlated with visual disease symptoms. Zhang et al (2019) reported that a phenotype derived from the regression of disease on relative maturity is an effective trait to detect scald resistance under natural field conditions when relative maturity is correlated with scald resistance, as it reduces the possiblity of confusing maturityrelated loci with true resistance loci.…”
Section: Ma Jor G Ene S and Lo CI Identified For Sc Ald Re S Is Tan Ce In Barle Ymentioning
confidence: 99%
“…The linear relationships between each of the four traits was determined from the trait: genotype covariance modelling using methods detailed in Zhang et al (2019) as follows:…”
Section: Phenotypic Data Analysismentioning
confidence: 99%